THE IMPACT OF PROBLEM BASED LEARNING (PBL) ON THE LEARNING OUTCOMES OF THE 7th GRADER ON THE MATERIAL SUBSTANCES AND THEIR CHANGES - Salvira, Muna; Az zahra, Firda; Muttaqiin, Arief; Azhar, Aulia (SEMESTA: Journal of Science Education and Teaching, 2025)
This research aims to ascertain the influence of the Problem Based Learning model on students’ learning outcomes of the 7th grader about the matter and its changes topic. This quasi-experimental research is to determine if a specific treatment has an effect on the group being studied. For this investigation, an uneven control group design will be employed. One sample strategy utilized in sampling techniques is purposive sampling. The Problem Based Learning model was employed in the experiment group, while the lecture approach was used in the control group. Based on the T-test hypothesis testing, it was demonstrated that there was a significant difference in average between the experimental class and the control class with Tcount = -24.0946 and Ttable = 2.0017, the results of the second similarity test in average post-test indicated that H0 was rejected or Ha was accepted. As a result, the Problem Based Learning Model significantly affects the students’ learning outcomes.